2021
DOI: 10.1186/s13550-021-00774-x
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of [18F]florbetaben textural features and age of onset of Alzheimer’s disease: a principal components analysis approach

Abstract: Background When Alzheimer’s disease (AD) is occurring at an early onset before 65 years old, its clinical course is generally more aggressive than in the case of a late onset. We aim at identifying [$$^{18}$$ 18 F]florbetaben PET biomarkers sensitive to differences between early-onset Alzheimer’s disease (EOAD) and late-onset Alzheimer’s disease (LOAD). We conducted [$$^{18}$$ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…In our study, as in several previous ones, 17,18 β-amyloid deposition did not significantly differ between EOAD and LOAD, indicating no close association between Aβ deposition and onset age. Conversely, others have reported that Aβ deposition is more pronounced in EOAD 11,18,36,37 . The discrepancy might be related to differences in group categorization, sample size, and methodology between studies.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…In our study, as in several previous ones, 17,18 β-amyloid deposition did not significantly differ between EOAD and LOAD, indicating no close association between Aβ deposition and onset age. Conversely, others have reported that Aβ deposition is more pronounced in EOAD 11,18,36,37 . The discrepancy might be related to differences in group categorization, sample size, and methodology between studies.…”
Section: Discussionmentioning
confidence: 87%
“…Conversely, others have reported that Aβ deposition is more pronounced in EOAD. 11,18,36,37 The discrepancy might be related to differences in group categorization, sample size, and methodology between studies.…”
Section: Discussionmentioning
confidence: 99%
“…It also reflects the degree of association between different voxels in the whole brain [41]. Previous study suggested that early onset of AD showed more complex pattern in T1W images [42]. GLRLM relates to the coarseness and complexity, which reflect the degree of association between different pixels in the whole brain [41].…”
Section: Radiomics Features In Ad MCI and Cnmentioning
confidence: 99%